2003
DOI: 10.1359/jbmr.2003.18.5.827
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinases Inhibit Bone Morphogenetic Protein-Smad Responsive Promoter Activity and Differentiation of Murine MC3T3-E1 Osteoblast-like Cells

Abstract: Growth factors such as fibroblast growth factor-2 (FGF-2) and epidermal growth factor (EGF) that activate extracellular signal-regulated kinases (ERKs) through receptor tyrosine kinases (RTKs) stimulate proliferation but suppress differentiation of osteoblasts. To study the mechanism of this inhibitory action of these growth factors on osteoblastic differentiation, we evaluated Smad1 transactivity in MC3T3-E1 osteoblast-like cells by reporters of promoter activity of mouse Smad6, an early response gene to bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
50
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 59 publications
(79 reference statements)
4
50
1
Order By: Relevance
“…Epidermal growth factor (EGF)-induced receptor tyrosine kinase activation suppresses BMP-2-induced differentiation of osteoblasts by interfering with Smad-1 activity (Nakayama et al, 2003). Integrin activation of focal adhesion kinase (FAK) induces Ras and the downstream Erk in ostoeblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGF)-induced receptor tyrosine kinase activation suppresses BMP-2-induced differentiation of osteoblasts by interfering with Smad-1 activity (Nakayama et al, 2003). Integrin activation of focal adhesion kinase (FAK) induces Ras and the downstream Erk in ostoeblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, we and others (56) did not observe inhibition of nuclear translocation of Smads in the presence of receptor tyrosine kinase signaling. Also, Nakayama et al (57) show that receptor tyrosine kinase signaling can suppress the transactivating properties of a Gal4-Smad1 chimeric protein that is constitutively nuclear. Furthermore, we found that the BMP-dependent gene expression was not generally suppressed as might be expected if nuclear translocation of Smads was absent.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the TGFb/ BMP antigrowth and Ras/MAP-K progrowth signalling pathways remains unclear, but there is recent evidence of crosstalk between them (Kretzschmar et al, 1997;Yue et al, 1999;Wach et al, 2001). While BMP-2 stimulation of osteoblasts leads to activation of Ras (Nakayama et al, 2003), in Xenopus, BMP-4-stimulated erythroid differentiation is inhibited by dominant-negative activation of the Ras pathway (Xu et al, 1996). SMAD7, one of the inhibitory SMADs of the BMP/TGFb signalling pathway, has been shown to cooperate with oncogenic Ras to escape growth arrest (Liu et al, 2003).…”
mentioning
confidence: 99%